Radiosynovectomy in pigmented villonodular synovitis - Kat, S.; Kutz, R.; Elbracht, T.; Weseloh, G.; Kuwert, T. (Nuklearmedizin - NuclearMedicine, 2000)
Background: Pigmented villonodular synovitis (PVS) is a very rare disorder characterized by a slowly progressive benign proliferation of synovial tissue. As yet, the mainstay of its treatment has been surgical or athroscopic synovectomy. However, the relapse rates reported are relatively high, ranging between 8% and 46%. The aim of this study was to evaluate the efficacy of a combined treatment with radiosynovectomy (RS) and surgical synovectomy. Method: We studied the effect of thirteen radiosynovectomies performed in eleven pigmented villonodular synovitis patients with Y-90 citrate or Re-186 sulfide. All patients had undergone intraarticular radiation therapy within 6 months after surgical synovectomy. Eight patients suffered from pigmented villonodular synovitis in the knee, the remaining three from pigmented villonodular synovitis in the hip. Two of eleven patients had to be treated twice, due to a relapse of symptoms occurring four months after the first treatment. Therapy responses were evaluated one year after the initial radiosynovectomy. Clinical response was assessed on three-point rating scales evaluating the degree of hydrops, rubor, and motility as well as the degree of pain, these four parameters were then averaged to an overall clinical score (CS). We also quantified the relative uptake of Tc-99m-diphosphonate in the joint involved on the blood pool (BUR) and delayed images (DUR). Results: Clinical score decreased from 5.45 ± 1.04 to 1.18 ± 1.16 at one year after treatment (p < 0.005), and the blood pool from 0.51 ± 0.36 to 0.08 ± 0.44 (p < 0.005). Delayed images were not significantly changed: 0.66 ± 0.71 versus 0.66 ± 0.73 (p = 0.3). Conclusion: A combination of surgical synovectomy with radiosynovectomy is highly efficacious in treating clinical symptoms of pigmented villonodular synovitis. It also improves bone scintigraphic signs of inflammation, but has no influence on late diphosphonate uptake.
Keywords: Radiosynovectomy; pigmented villonodular synovitis; radionuclide therapy